Early Detection of Non-Small Cell Lung Cancer by Using a 12-microRNA Panel and a Nomogram for Assistant Diagnosis - Wang, Weidong; Chen, Dongni; Chen, Weiwei; Xin, Ziya; Huang, Zirui; Zhang, Xuewen; Xi, Kexing; Wang, Gongming; Zhang, Rusi; Zhao, Dechang; Liu, Li; Zhang, Lanjun (Frontiers in Oncology, 2020)
Background: We previously identified a 12-miRNA panel (miRNA-17, miRNA-146a, miRNA-200b, miRNA-182, miRNA-155, miRNA-221, miRNA-205, miRNA-126, miRNA-7, miRNA-21, miRNA-145, and miRNA-210) that aided in the early diagnosis of non-small cell lung cancer (NSCLC). We validated the diagnostic value of this miRNA panel and compared it with that of traditional tumor markers and radiological diagnosis. We constructed a nomogram based on the miRNA panel’s results to predict the risk of NSCLC. Methods: Eighty-two participants with pulmonary nodules on a CT scan and who underwent a pathological examination and surgical treatment were enrolled in our study. Patients were randomly divided into a training or validation group. miRNA concentrations were quantitated by RT-PCR and log transformed for analysis. The cutoff value was determined in the training group and then applied in the validation group. A comparison between the miRNAs and traditional tumor markers (CEA, NSE, and Cyfra21-1) and radiological diagnosis was performed. A nomogram based on the miRNA panel’s results to predict the risk of NSCLC was constructed. Results: The expression level of these 12 miRNAs were significantly higher in NSCLC patients than in benign patients. In the validation group, the specificity and positive predictive value were 96.4% and 95.8%, respectively, which were significantly higher than those using traditional tumor markers or radiological diagnosis. The sensitivity was 42.6%, which was also higher than that using tumor markers. Moreover, the sensitivity increased to 63.6% when the nodule diameters were larger than 2 cm. The miRNAs and 7 clinical factors were integrated into the nomogram, and the calibration curves showed optimal agreement between the predicted and actual probabilities. Conclusions: Our miRNA panel has clinical value for the early detection of NSCLC. A nomogram was constructed and internally validated, and the results indicate that it can assist clinicians in making treatment recommendations in the clinic.